What have you tried? Let me restate it for you: Let r,s,t be the remainders when a,b,(a+b) are divided by n respectively. Then the remainder when r+s is divided by n is equal to t.
If x= a+ b (mod n) then x= kn+ a+ b for some integer k. Choose any integer i and define j= k- i then k= i+ j so x= kn+ a+ b= (i+ j)n+ a+ b= in+ jn+ a+ b= (in+ a)+ (jn+ b)
This site uses cookies to help personalise content, tailor your experience and to keep you logged in if you register.
By continuing to use this site, you are consenting to our use of cookies.